ДЕЯТЕЛЬНОСТЬ ЮРИЯ КРИЖАНИЧА В КОНТЕКСТЕ УКРАИНСКОГО БАРОККО (Philological Studies, 2019)
Ukrainian component – a significant part of the enlightened knowledge of Slavic Croat. Krizhanich communication with Ukraine regularity manifestation of specificity of the Ukrainian baroque, primarily as a system, the participation of its representatives in the cultural processes from western to eastern Slavic spaces. His ideas received understanding and support in the Ukrainian environment also because cognation beliefs, desires to unite with various baroque centers of Europe – from western to eastern.
Keywords: Krizhanich, Ukrainian Baroque, Croatia, Church Union, Baroque Slavism